2020
DOI: 10.1177/1356336x20980777
|View full text |Cite
|
Sign up to set email alerts
|

The relationships among personal accomplishment, resilience and teachers’ experience of teaching multiple school subjects role conflict

Abstract: This study develops an understanding of the relationships among personal accomplishment, resilience, and teaching multiple school subjects role conflict (TMSS-RC) among Irish post-primary, multi-subject teachers. A theoretically informed conceptual framework was developed to explain the relationships among personal accomplishment, resilience, and the sub-domains of TMSS-RC: status conflict, schedule conflict, and energy expenditure. Participants included 259 post-primary teachers across Ireland who were respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 70 publications
0
7
0
1
Order By: Relevance
“…The Pearson correlation found that the variables had a moderate relationship. One of the most important aspects of a professional teacher is having proper academic knowledge and presenting concepts effectively (Iannucci et al, 2021). We may encounter a variety of methods for teaching or presenting concepts in the classroom, but proper illustrations and supported teaching aids can help us choose the method that is basic but effective in terms of clarity and long-term recall.…”
Section: Resultsmentioning
confidence: 99%
“…The Pearson correlation found that the variables had a moderate relationship. One of the most important aspects of a professional teacher is having proper academic knowledge and presenting concepts effectively (Iannucci et al, 2021). We may encounter a variety of methods for teaching or presenting concepts in the classroom, but proper illustrations and supported teaching aids can help us choose the method that is basic but effective in terms of clarity and long-term recall.…”
Section: Resultsmentioning
confidence: 99%
“…One would expect that the increase in scores for indicators should gradually increase as the age and experience of the participants increase. However, in reality this is not the case, the formation of individual components of emotional flexibility occurs unevenly, and this effect cannot be explained by the personal characteristics of each participant, because significant differences are observed not within groups by years of study, but between these groups (Iannucci et al, 2021 ; Kashdan et al, 2020 ). Similar effects were indicated by a number of researchers who were involved in the processes of psychological adaptation and coping (Coyne et al, 2021 ; Doorley et al, 2020 ; Sheppes, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A distinctive feature of most studies on this topic is the use of two terms to define flexibility: flexibility itself and variability, which means versatility. Several works of researchers of different countries distinguish two substructures of emotional flexibility: emotional stability and positive emotional expressiveness, which are interdependent (Iannucci et al, 2021 ; Mitina, 2020 ; Pruessner et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The compilation of professional teaching materials and the augmentation of resources dedicated to mathematics instruction stand out as strategies that can contribute to the enhancement of educators’ intellectual capabilities ( Meyer & Aikenhead, 2021 ). Iannucci, Richards & MacPhail (2021) investigated the interconnections between individual achievement, psychological resilience, and the multifaceted role conflicts experienced by educators. Employing parallel confirmatory factor analysis, the researchers substantiated the psychometric integrity of the proposed factor framework ( Iannucci, Richards & MacPhail, 2021 ).…”
Section: Recent Related Workmentioning
confidence: 99%
“… Iannucci, Richards & MacPhail (2021) investigated the interconnections between individual achievement, psychological resilience, and the multifaceted role conflicts experienced by educators. Employing parallel confirmatory factor analysis, the researchers substantiated the psychometric integrity of the proposed factor framework ( Iannucci, Richards & MacPhail, 2021 ). The hypothesized model demonstrated a favorable fit with the empirical data.…”
Section: Recent Related Workmentioning
confidence: 99%